2016
DOI: 10.1038/srep38262
|View full text |Cite
|
Sign up to set email alerts
|

Blood hsa-miR-122-5p and hsa-miR-885-5p levels associate with fatty liver and related lipoprotein metabolism—The Young Finns Study

Abstract: MicroRNAs are involved in disease development and may be utilized as biomarkers. We investigated the association of blood miRNA levels and a) fatty liver (FL), b) lipoprotein and lipid pathways involved in liver lipid accumulation and c) levels of predicted mRNA targets in general population based cohort. Blood microRNA profiling (TaqMan OpenArray), genome-wide gene expression arrays and nuclear magnetic resonance metabolomics were performed for Young Finns Study participants aged 34–49 years (n = 871). Liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 64 publications
2
61
0
1
Order By: Relevance
“…In particular, once validated, circulating miR-122 appears to be a promising functional biomarker, able to sense changes in hepatic metabolism as well as to induce them. In support of this hypothesis, an association of miR-122-5p with fatty liver and related lipoprotein metabolism was recently described in a Finnish general population cohort (15). This reinforces the concept that increased circulating miR-122 might flag a problem with liver metabolisms and require further laboratory and clinical analyses going beyond the normal routine.…”
supporting
confidence: 65%
“…In particular, once validated, circulating miR-122 appears to be a promising functional biomarker, able to sense changes in hepatic metabolism as well as to induce them. In support of this hypothesis, an association of miR-122-5p with fatty liver and related lipoprotein metabolism was recently described in a Finnish general population cohort (15). This reinforces the concept that increased circulating miR-122 might flag a problem with liver metabolisms and require further laboratory and clinical analyses going beyond the normal routine.…”
supporting
confidence: 65%
“…We found that exosomal miR‐122‐5p is associated with obesity. Circulating miR‐122‐5p is associated with fatty liver and lipoprotein metabolism and is being considered as a marker for acute myocardial infarction . Antagonizing miR‐122 levels in vivo decreases cholesterol levels and increases hepatic fatty acid oxidation .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple previous studies have been focused on discriminating various NAFLD stages by analyzing miRNA expression profiles in liver parenchyma ( Guo et al, 2016 ; Soronen et al, 2016 ; Latorre et al, 2017 ). However, only several research groups have so far investigated NAFLD-associated changes in the spectrum of extracellular miRNAs present in human blood ( Cermelli et al, 2011 ; Yamada et al, 2013 ; Miyaaki et al, 2014 ; Tan et al, 2014 ; Becker et al, 2015 ; Pirola et al, 2015 ; Akuta et al, 2016 ; Liu et al, 2016 ; Raitoharju et al, 2016 ; Salvoza et al, 2016 ; Thompson et al, 2017 ) ( Table 1 ). These reports strongly suggest that circulating miRNAs can be utilized as more sensitive and specific biomarkers of liver damage as compared to currently employed biochemical tests based on measuring the relative activity of serum transaminases.…”
Section: Extracellular Circulating Mirna Profiles For the Diagnosis Omentioning
confidence: 99%
“… Raitoharju et al (2016) reported the association of blood miR-122 and miR-885 concentrations with ultrasonically assessed fatty liver in Finns study participants aged 34–49 years. As this study cohort was unusually large, the confidence of the reported findings was impressive; thus, Bonferroni-corrected p -values for miR-122 and miR-885 constituted 1.92 × 10 -15 and 2.58 × 10 -4 , respectively.…”
Section: Extracellular Circulating Mirna Profiles For the Diagnosis Omentioning
confidence: 99%
See 1 more Smart Citation